2019
DOI: 10.3390/ijerph16101802
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Biomarkers Used for Assessing Human Exposure to Metals from E-Waste

Abstract: Electronic waste recycling presents workers and communities with a potential for exposures to dangerous chemicals, including metals. This review examines studies that report on blood, hair, and urine biomarkers of communities and workers exposed to metals from e-waste. Our results from the evaluation of 19 publications found that there are consistently elevated levels of lead found in occupationally and non-occupationally exposed populations, in both the formal and the informal e-waste recycling sectors. Vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…This may prevent e-waste from being dumped in, and also outside, European countries and would support more sustainable processing of this waste stream in line with the Basel Convention on the Control of Transboundary Movement of Hazardous Wastes and their Disposal [ 18 ]. A recent literature review by Arain and Neitzel (2019) [ 19 ] showed that, so far, occupational exposures occurring in this sector were only studied in one European country [ 20 ]. We identified a second study also reporting on the use of biomonitoring to assess the level of exposure to metals [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…This may prevent e-waste from being dumped in, and also outside, European countries and would support more sustainable processing of this waste stream in line with the Basel Convention on the Control of Transboundary Movement of Hazardous Wastes and their Disposal [ 18 ]. A recent literature review by Arain and Neitzel (2019) [ 19 ] showed that, so far, occupational exposures occurring in this sector were only studied in one European country [ 20 ]. We identified a second study also reporting on the use of biomonitoring to assess the level of exposure to metals [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our study also represents an important expansion in e-waste research beyond the countries where most similar research has been done (eg, China, India, and Ghana). 6,38,39 In conclusion, our study showed that longer working hours and smoking contribute to increased exposures to a number of metals among informal male e-waste recycling workers in Thailand, and an association between metal exposures and increased oxidative stress and renal markers among female e-waste recyclers. Given these results, health promotion effortsincluding smoking cessation-should be directed to these workers to improve their health and prevent disease.…”
Section: Take-home Messagementioning
confidence: 53%
“…It indicates that the research hotspot should include e-waste, heavy metal exposure, and the corresponding management. Future research directions may include the exposure probability of occupational and non-occupational groups, the exposure probability and degree of different occupational groups, the application of nanomaterials and other emerging materials to replace heavy metal materials in electronic products, and the development of environmentally friendly and effective recycling methods for electronic pollutants ( 56 ). There has been an increase in the attention paid to biohydrometallurgy because the main advantages of biohydrometallurgy compared to other methods include low operating and maintenance costs, a low energy input, the use of natural resources such as air and water, a low environmental impact, and operation at ambient temperature and pressure, which is more in line with the principles of the circular economy ( 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…Then, we analyzed the organization's co-authorship of over five papers and obtained the results for 42 institutions. The top five institutions in terms of the strength of their total links were Jinan University (59), Shantou University (58), the Chinese Academy of Sciences (56), the University of Ghana (30), and the University of Chinese Academy of Sciences (20; Table 3, Figure 5A). Over time, the average years of contributions in this field by these organizations are closer to the recent, such as Nanjing Medical University, Guangdong University of Technology, South China Normal University, Synergy Innovation Institution GDUT, Kwame Nkrumah University of Science and Technology, the Academy of Scientific and Innovative Research, and so on (Figure 5B).…”
Section: Organizations and Source Analysismentioning
confidence: 99%